Pengaruh Digital Payment dan E-Service Quality Terhadap Perilaku Konsumtif pada Pengguna Shopee Wilayah DKI Jakarta - Naufalia, Viani (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2022)
The current condition of the Covid-19 pandemic which is also experienced by Indonesia has made many changes to people's activities, one of which is the change in people's shopping activities only through the internet. However, this also makes people in Indonesia more consumptive, because of the ease of shopping offered to the public. The purpose of this study is whether there is an influence of digital payment and e-service quality on the consumptive behavior of the community. Primary data was obtained through a questionnaire consisting of 3 variables using a Likert scale on 50 respondents, namely Shopee users in the DKI Jakarta area with purposive sampling technique. The data analysis techniques used included validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, simple linear regression analysis test, partial t-test, simultaneous f-test and coefficient of determination test. This study resulted in a positive influence between digital payment variables on consumptive behavior of 12.7%. Then, there is a positive influence between the variables of e-service quality on consumptive behavior of 1.4%. Also, there is a positive influence between the digital payment and e-service quality variables simultaneously on consumptive behavior, namely 13.7%. This study provides theoretical implications in the form of references for further related research, and as evaluation material and suggestions for business actors as well as for the community as readers of this research.